Transboundary extraction of groundwater in the presence of hydraulic fracturing. (22nd May 2019) - Poudel, Biswo N.; Paudel, Krishna P.
Abstract: We studied transboundary groundwater management problems in the presence of hydraulic fracturing. We found that the presence of risk suggests there should be caution when considering hydraulic fracturing. Our results from the cooperative solution show a decrease in hydraulic fracturing and increase in the steady state survival rate of groundwater. We also provide a Pigouvian type tax that could be imposed on natural gas developers. RECOMMENDATION FOR RESOURCE MANAGERS: Hydraulic fracturing has the potential to impact groundwater quantity and quality. A tax on hydraulic fracturing activity has the potential to reduce economic damage. If two competing states that share groundwater resources cooperate and form a compact, this will reduce hydraulic fracturing activities and increase groundwater quality and quantity. It is necessary to calculate the total cost and benefit of hydraulic fracturing before considering regulations.